Thermoplasmonic nano-rupture of cells reveals annexin V function in plasma membrane repair. Issue 21 (5th May 2022) - Moreno-Pescador, Guillermo S.; Aswad, Dunya S.; Florentsen, Christoffer D.; Bahadori, Azra; Arastoo, Mohammad R.; Danielsen, Helena Maria D.; Heitmann, Anne Sofie B.; Boye, Theresa L.; Nylandsted, Jesper; Oddershede, Lene B.; Bendix, Poul Martin
Abstract : Living cells respond to nanoscopic thermoplasmonic injury by recruiting an annular ring of annexin V. Abstract : Maintaining the integrity of the cell plasma membrane (PM) is critical for the survival of cells. While an efficient PM repair machinery can aid survival of healthy cells by preventing influx of extracellular calcium, it can also constitute an obstacle in drug delivery and photothermal therapy. We show how nanoscopic holes can be created in a controlled fashion to the cell's plasma membrane, thus allowing identification of molecular components which have a pivotal role in PM repair. Cells are punctured by laser induced local heating of gold nanostructures at the cell surface which causes nano-ruptures in cellular PMs. Recruitment of annexin V near the hole is found to locally reshape the ruptured plasma membrane. Experiments using model membranes, containing recombinant annexin V, provide further biophysical insight into the ability of annexin V to reshape edges surrounding a membrane hole. The thermoplasmonic method provides a general strategy to monitor the response to nanoscopic injuries to the cell surface which offer new insight into how cells respond to photothermal treatment.